PENERAPAN LESSON STUDY UNTUK MENINGKATAN KEMAMPUAN MENGAJAR MAHASISWA CALON GURU FISIKA - Handayani, Rif’ati Dina; Ryskiadi, Agung; Machrus, Ali; Acik, Rifan (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2015)
Lesson study is a development model for educators through sustainable andÂ collaborative learning. Lesson study was conducted in three phases, namely the plan, do, see phase, in which these phases were implemented in a structured, cyclical and continuous manner. In this study, the subject of lesson study implementation were four Physics pre- service conducted teaching practice in one of public junior high schools in Bondowoso. Results showed that lesson study implementation enhance these physics pre-service teachers teaching ability from poor to excellent.Keywords: Lesson Study, Pre-service Physics Teacher, Teaching AbilityABSTRAKLesson study merupakan suatu model pengembangan kemampuan mengajar melalui pengkajian pembelajaran secara kolaboratif dan berkelanjutan. Lesson study dilaksanakan dalam tiga tahapan, yaitu plan, do, see yang dilaksanakan secara terstruktur, bersiklus dan berkelanjutan. Dalam penelitian ini subjek dari pelaksanaan lesson study adalah empat orangÂ mahasiswa calon guru fisika yang sedang melaksanakan PPL di salah satu SMP Negeri di Bondowoso. Hasil penelitian menunjukkan bahwa penerapan lesson study dapat meningkatkan kemampuan mengajar mahasiswa calon guru fisika dari kriteria kurang baik menjadi kriteria sangat baik.Kata kunci: Calon guru fisika, Lesson Study, Kemampuan Mengajar